Multiculturalism and multicultural education: A case study of teacher candidates’ perceptions - Fatih Yılmaz (Cogent Education, 2016)
The main purpose of the research was to determine the multiculturalism and multicultural education perceptions of teacher candidates. The research was designed as qualitative within this context and was patterned as a case study. The research data were obtained from the semi-structured interviews performed with 12 teacher candidates. In this research, teacher candidates evaluate the concept of multiculturalism positively because of the social structure. But, they are also aware of the importance of teacher education in the preparation of this infrastructure. The results of the study showed that especially in the transition of multicultural education, the teachers have primary responsibilities. And in this study, it also seemed that teacher education and teachers’ positive attitudes toward multicultural education have an important role to live together; to be peaceful and respectful; to accept all identities with their cultural properties without fear of the country’s separation.